The Stola Symbol of GKPB (Protestant Christian Church in Bali): A Landscape Linguistic Study - I Gede Neil Prajamukti Wardhana; Ni Made Diana Erfiani; Ni Luh Desy Suari Dewi (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2026)
This study is discussed the symbolic and linguistic dimensions of the stola as a liturgical vestment within the Christian Protestant Church in Bali (GKPB), emphasized its role in articulating theological meaning and ecological identity. This method uses a qualitative descriptive methodology; the research was conducted at GKPB Hosana Kwanji, Bali and involved participatory observation, in-depth interviews with pastors and church council members, and document analysis of visual and textual materials. The participants included Elders, Deacons, and Evangelists who wear Stolas during worship services. The data was found through semiotic frameworks, specifically Peirce’s triadic model and Saussure’s dyadic model, to interpret the embedded symbols. The findings revealed three distinct symbolic patterns: grapes and chalice for Elders (representing communion and fellowship), bread and fish for Deacons (signifying service and provision), and rice for Evangelists (symbolizing sowing and evangelism). These symbols were not only delineated liturgical roles but also reflected Balinese ecological metaphors and cultural narratives. This study is concluded that the GKPB stola served as a place-based religious symbol, integrating Christian theology with local environmental and cultural contexts. Through eco-linguistic and semiotic analysis, the research showed that how visual and linguistic elements construct a contextualized Christian identity that resonates with Bali’s natural landscape and spiritual heritage.